Keberhasilan Penyuluhan Kesehatan Gigi Dan Mulut Dengan Modifikasi Metode Makaton Dalam Meningkatkan Kemampuan Menggosok Gigi Secara Mandiri Pada Penderita Retardasi Mental Di SLB Harmony Surakarta - Perwidananta, Readilkha; , Dwi Kurniawati, S.KG, MPH (2016)
Background: Bad oral hygiene was problem which is commonly found in patients with mental retardation. This happens due to inability people with mental retardation for brushing teeth independently because of intellectual and adaptif malfunction. Modification of makaton method was form of delivery information using makaton that modified with adding children's song in the form of symbol about explanations teeth areas that brushed in the form of video animation and combined with props then followed by demonstration of brushing teeth correctly. Purpose: to know the success of dental health education using modification of the makaton method to increase the ability of independently brushing teeth in people with mental retardation in SLB Harmony Surakarta. Method: quasi-experimental study used one group pre and post test. Subjects as much as 14 people with mental retardation who had categories of feeble minded and imbecile. This research was dental health education for 20 days starting with the pre-test and post-test. The method of dental health education used modification of makaton method then evaluated daily to see improvement ability to brush their teeth. Improvement ability of brushing teeth can be known from how many teeth areas surface can be brushed by people with mental retardation correctly independently. Results: The results of the Wilcoxon test showed p value = 0.001 (p <0.05), which mean that there was significant difference between the data before and after education with modification of makaton method.